Facilitation of holm oak recruitment through two contrasted shrubs species in Mediterranean grazed woodlands - Rolo, Víctor; Plieninger, Tobias; Moreno, Gerardo (Journal of Vegetation Science, 2012)
Question: Regeneration failure and gradual tree dieback are major threats for the persistence of savanna-like grazed oak woodlands. Current research has argued that the scarcity of ‘safe sites’, in particular shrubs, is the main cause of the lack of effective tree recruitment. But can different shrub species be considered as safe sites generally? Do two distinct shrub species, with contrasted life strategies, affect several life stages of tree regeneration in similar ways or do they speciﬁcally inﬂuence the recruitment process? Location: Holm oak woodlands of SW Iberian Peninsula (40°02′ N, 06°06′ W). Methods: We surveyed densities of recently emerged and surviving seedlings as well as small and large saplings over two consecutive years in 40 sites that were independently managed, comparing plots encroached by either Cistus ladanifer (a shallow-rooted shrub, forming dense populations, with reported allelopathic compounds) or Retama sphaerocarpa (a N2-ﬁxing, deep-rooted shrub that forms scattered populations) vs their respective control plots (without shrubs). To assess the effect of mature trees and both shrub species on the performance and survival of recently emerged oak seedlings, we established an acorn sowing experiment in the same surveyed microhabitats (open spaces, shrub, tree and tree–shrub). Results: The survey showed that both shrubs species had a positive effect at early recruitment stages. At later life stages, this effect weakened under Cistus whereas it strengthened under Retama. The acorn sowing experiment showed that both shrub species buffered abiotic conditions and enhanced seedling functioning similarly, but Retama enhanced seedling survival to a higher extent than Cistus. Conclusions: The two shrub species impose a speciﬁc template that is able to affect the long-term dynamics of Mediterranean oak woodlands. Cistus shrubs are effective in protecting seedlings physically against herbivores and facilitate early survival, but may compete with older stages of oak regeneration. In contrast, Retama shrubs exert stronger biological facilitation and guarantee longterm persistence of surviving seedlings. We argue that improved understanding of the effectiveness of different nurse plants and their contrasting factors is of major interest for the conservation and restoration of degraded oak woodlands
Keywords: Cistus ladanifer; Dehesa; nurse plant; Quercus ilex; retama sphaerocarpa; Shrub encroachment

Methods to improve the recruitment of holm-oak seedlings in grazed Mediterranean savanna-like ecosystems (dehesas) - Leiva, María José; Mancilla-Leyton, Juan Manuel; Martín-Vicente, Ángel (Annals of Forest Science, 2012)
& Context “Dehesas” are savanna-like ecosystems of human origin that extend broadly in the Mediterranean area of the Iberian Peninsula. They consist of scattered oaks (mainly Quercus ilex subsp. ballota L. holm-oak), an annual grassland layer and interspersed shrubs. These ecosystems, used for grazing and wild game, support high plant and animal biodiversity and provide important environmental services. At present, Mediterranean “dehesas” are endangered by the lack of oak regeneration. & Aims This paper analyses the efficiency of: (1) using shrubs as nurse plants; (2) drip irrigation of seedlings during summer; and (3) a combination of the two methods for the restoration of a “dehesa” in a mid-mountain Mediterranean area of southern Spain. & Methods Different techniques were tested to improve the recruitment of holm-oak seedling during a 3-year field experiment: (1) acorn plantation in open spaces, irrigating seedlings during the first dry season; (2) acorn plantation beneath the canopy of Myrtus communis L. and (3) both methods combined. & Results There was a large facilitative effect of myrtle for the recruitment of holm-oak seedlings, regardless of the supply of irrigation. This effect was associated with a large decrease in air temperature and photosynthetically active radiation beneath myrtle canopies. By contrast, summer irrigation of seedlings planted in open spaces did not improve seedling survival after 3 years despite a small and transient positive effect on seedling survival during the 1st year. & Conclusion The use of evergreen shrubs, such as myrtle, as nurse plants may be considered to restore “dehesas” instead of expensive seedling irrigation techniques. Several studies have promoted abandoning grazing to increase holm oak selfregeneration in “dehesas”. However, creating closed patches of naturally occurring evergreen shrubs could provide suitable sites for oak planting when necessary, thus enhancing seedling recruitment without damaging the environmental and economic value of these ecosystems.
Keywords: nurse plant; Photosynthetically active radiation; seedling emergence timing; seedling longevity; summer drip-irrigation of seedlings

Methods to improve the recruitment of holm-oak seedlings in grazed Mediterranean savanna-like ecosystems (dehesas) - Leiva, María José; Mancilla-Leyton, Juan Manuel; Martín-Vicente, Ángel (Annals of Forest Science, 2012)
& Context “Dehesas” are savanna-like ecosystems of human origin that extend broadly in the Mediterranean area of the Iberian Peninsula. They consist of scattered oaks (mainly Quercus ilex subsp. ballota L. holm-oak), an annual grassland layer and interspersed shrubs. These ecosystems, used for grazing and wild game, support high plant and animal biodiversity and provide important environmental services. At present, Mediterranean “dehesas” are endangered by the lack of oak regeneration. & Aims This paper analyses the efficiency of: (1) using shrubs as nurse plants; (2) drip irrigation of seedlings during summer; and (3) a combination of the two methods for the restoration of a “dehesa” in a mid-mountain Mediterranean area of southern Spain. & Methods Different techniques were tested to improve the recruitment of holm-oak seedling during a 3-year field experiment: (1) acorn plantation in open spaces, irrigating seedlings during the first dry season; (2) acorn plantation beneath the canopy of Myrtus communis L. and (3) both methods combined. & Results There was a large facilitative effect of myrtle for the recruitment of holm-oak seedlings, regardless of the supply of irrigation. This effect was associated with a large decrease in air temperature and photosynthetically active radiation beneath myrtle canopies. By contrast, summer irrigation of seedlings planted in open spaces did not improve seedling survival after 3 years despite a small and transient positive effect on seedling survival during the 1st year. & Conclusion The use of evergreen shrubs, such as myrtle, as nurse plants may be considered to restore “dehesas” instead of expensive seedling irrigation techniques. Several studies have promoted abandoning grazing to increase holm oak selfregeneration in “dehesas”. However, creating closed patches of naturally occurring evergreen shrubs could provide suitable sites for oak planting when necessary, thus enhancing seedling recruitment without damaging the environmental and economic value of these ecosystems.
Keywords: nurse plant; Photosynthetically active radiation; seedling emergence timing; seedling longevity; summer drip-irrigation of seedlings